Waliyullah Al-Dahlawi Muhadditsan - Ikhsan Nur (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2022)
Allah swt expressly conveys that "and indeed We are the ones who guard it (the Qur'an)", but to protect the prophet's hadith from changes in the eyes, false reliance on the name of the prophet or the occurrence of errors in the chain of hadith narration, Allah assigns this task to Muslims more precisely. to hadith scholars. In a hadith narrated by Abu daud "the Prophet SAW said: "Verily Allah will send for this Ummah, at the end of every hundred years, people who will renew their religion". With their diligence, thoroughness and hard work, the traditions that came from the prophet to us today. In the course of Islamic history, various regions seem to share and change roles in reviving the sunnahs of the prophet Muhammad SAW. When the movement for the study of Sunnah in one area declines due to various factors, then other parts of the region will immediately rise to shine brightly in other areas. India or what is known as Al-Hindi has also been transformed into an influential center of Islamic studies, this situation has been going on since the 12th century Hijri. The study of Hadith became one of the most advanced fields in the Indies. These scholars had a major role in the study of hadith such as ahkam hadiths, sanad criticism, ilat hadith, syarah hadith and various other themes. Among the most famous hadith scholars from India is Shaykh Abdurrahim Ad-Dahlawi. Many important writings in the field of hadith that he produced during his life, such as his contribution to the development of hadith in India and other Islamic worlds. He was also a hadith reference in his time and also printed the names of several other great hadith scholars. Here the author will discuss his biography, scientific journey, hadith teachers, famous students in the field of hadith, as well as his work and methods in the field of hadith.ABSTRAKSecara tegas Allah swt menyampaikan bahwa “dan sesungguhnya Kami lah yang menjaganya (al-Quran)”, namun untuk menjaga hadis nabi dari perubahan matan, penyandaran yang palsu atas nama nabi atau terjadinya kesalahan pada sanad periwayatan hadis, Allah bebankan tugas ini kepada umat Islam lebih tepatnya kepada ulama hadis. Dalam sebuah hadis yang diriwayatkan oleh Abu daud, Nabi SAW bersabda : “Sesungguhnya Allah akan mengutus untuk umat ini, pada setiap akhir seratus tahun, orang yang akan memperbaharui  agamanya”. Dengan ketekunan, ketelitian dan kerja keras mereka hadis-hadis yang berasal dari Nabi sampai kepada kita saat ini. Dalam perjalanan sejarah Islam, berbagai wilayah seolah saling berbagi dan berganti peran dalam menghidupkan sunnah-sunnah Nabi Muhammad SAW. Ketika gerakan kajian sunnah di suatu wilayah menurun karena berbagai faktor, maka wilayah bagian yang lain akan segera bangkit bersinar menerangi wilayah lainnya. India atau yang disebut dengan Al-Hindi juga pernah menjelma menjadi pusat kajian Islam yang berpengaruh, keadaan ini berlangsung sejak abad ke-12 Hijriyah. Kajian hadis menjadi salah satu bidang yang paling maju di Hindia, para ulama ini memiliki peranan besar dalam kajian hadis seperti hadis-hadis ahkam, kritik sanad, ilat hadis, syarah hadis dan berbagai tema yang lain. Diantara ulama hadis yang paling terkenal dari India adalah Syaikh Waliyullah Abdurrahim Ad-Dahlawi. Banyak karya tulis penting di bidang hadis yang beliau hasilkan selama hidupnya, sebagai sumbangsih beliau untuk perkembangan hadis di India dan dunia Islam lainnya. beliau juga menjadi rujukan hadis pada masanya dan juga mencetak beberapa nama ulama besar hadis lainnya. Disini penulis akan membahas biografi, perjalanan ilmiah beliau, guru-guru hadis, murid-murid yang masyhur dalam bidang hadis, serta karya dan metode beliau dalam bidang hadis.